The Role of Settings in the Selected Works of Golden-Age Detective Fiction - Stýblová, Žaneta (Univerzita Pardubice, 2018)
This diploma thesis focuses on the setting in selected detective novels by two authors belonging to the so-called Golden Age of British crime fiction. First two chapters of the theoretical part summarize the history and definitions of detective novels, then the Golden Age and writers Agatha Christie and Margery Allingham are discussed. The third chapter is devoted solely to the setting in detective novels, its definitions and the theory connected to it. The last chapter of the theoretical part discusses the differences between the rural and urban setting. Subsequently, the country-house setting and the urban setting are analysed in five selected detective novels and their differences and similarities are compared based on the knowledge obtained in the theoretical part of the work.
Důležitost místa/lokality v klasické britské detektivce
Keywords: detektivní romány; zlatý věk; Christie, Agatha; Allingham, Margery; prostředí; venkovský dům; město; detective novels; Golden Age; Christie, Agatha; Allingham, Margery; setting; country house; city